The use of coercion against people with disabilities in community settings in Iceland - Salka Ósk Árnadóttir 1997- (2024)
A survey was conducted on the extent of coercion in services for disabled people in Iceland. The participation of municipalities and private entities throughout the country that provide services to the disabled was requested. A link to the questionnaire was sent to 142 head of homes who are in charge of residential services in Iceland asking about the prevalence and forms of coercion and the attitude of the directors towards the education and training of staff to deal with situations where coercion is used. The response rate was 59%. The main results of the survey are that in the last six months, coercion has been used in some form in 52% of homes in community settings in Iceland. The most common forms of coercion are remote monitoring devices and restrictions on a person's possessions. In most cases, authorization for the use of coercion will be obtained from the Exceptions Committee. The thesis presents the results and discusses various ethical issues related to the use of coercion in the service of disabled people. The importance of strengthening basic services for people with disabilities and reducing the use of coercive methods in services for people with disabilities is pointed out. Keywords: coercion, disabled people, questionnaire, ethical issues. Könnun var gerð á umfangi nauðungar í þjónustu við fatlað fólk á Íslandi. Óskað var eftir þátttöku sveitarfélaga og einkaaðila um land allt sem veita fötluðum þjónustu. Hlekkur á spurningakönnuna var sendur til 142 forstöðumanna sem eru yfir búsetuþjónustu á Íslandi þar sem spurt var um algengi og form nauðungar og viðhorf forstöðufólks til fræðslu og þjálfunar starfsfólks til að takast á við aðstæður þar sem nauðung er notuð. Svarprósentan var 59%. Helstu niðurstöður könnunarinnar eru að á síðustu 6 mánuðum hefur að nauðung verið notuð í einhverju formi hjá 52% forstöðumönnun í búsetuþjónustu fatlaðra á Íslandi. Algengasta form nauðungar er fjarvöktunarbúnaður og takmörkum á eigum þjónustunotenda. Í flestum tilfellum efur fengist heimild fyrir beitingu ...